2010
DOI: 10.1111/j.1460-9568.2010.07190.x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine‐vasopressin and the regulation of aggression in female Syrian hamsters (Mesocricetus auratus)

Abstract: Arginine-vasopressin (AVP) is critical for the expression of a variety of social behaviors in many species. Previous studies have demonstrated that AVP regulates behaviors such as social communication and aggression in Syrian hamsters through the V1a receptor subtype. In male hamsters, AVP injected into the anterior hypothalamus (AH) stimulates aggression, while injection of a V1a receptor antagonist inhibits the behavior. The purpose of the present studies was to determine whether AVP influences aggression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 40 publications
3
54
0
1
Order By: Relevance
“…Interestingly, the factorial analyses performed in the stress group showed that postpartum AVP levels loaded in the same factor as maternal and non-maternal related aggression but inversely (i.e., the lower AVP, the higher the aggression). The only study to our knowledge (Gutzler et al, 2010) that investigated the role of AVP in non-maternal related aggression in female rodents found that injection of AVP, and the V1a antagonist, into the anterior hypothalamus reduces and increases, respectively, offensive aggression in female hamsters; in contrast to the opposite effects that the same treatments induce in males. A similar AVP sex-dependent effect has been reported in humans (Thompson et al, 2006), in men intranasal administration of AVP decreases perception of friendliness in the faces of unfamiliar men, while the same treatment in women induces the opposite effect.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, the factorial analyses performed in the stress group showed that postpartum AVP levels loaded in the same factor as maternal and non-maternal related aggression but inversely (i.e., the lower AVP, the higher the aggression). The only study to our knowledge (Gutzler et al, 2010) that investigated the role of AVP in non-maternal related aggression in female rodents found that injection of AVP, and the V1a antagonist, into the anterior hypothalamus reduces and increases, respectively, offensive aggression in female hamsters; in contrast to the opposite effects that the same treatments induce in males. A similar AVP sex-dependent effect has been reported in humans (Thompson et al, 2006), in men intranasal administration of AVP decreases perception of friendliness in the faces of unfamiliar men, while the same treatment in women induces the opposite effect.…”
Section: Discussionmentioning
confidence: 83%
“…The use of highly resistive water improves the signalto-noise ratio of the electrical field generated during swimming and escape behavior by preventing dissipation of the electrical signals. Previous reports have shown that highly resistive water, such as that used in this study, did not have any obvious impact on the behavior or stress level of the animals (larvae and adults), even after an extended and continuous exposure of 3 d (Issa et al, 2011;Monesson-Olson et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we investigated how social regulation affects the activation patterns of escape and swim behaviors by using a noninvasive technique to monitor the patterns in freely behaving animals (Issa et al, 2011). We show that these neural circuits shift their activation with changes in the animal's social status.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as in crayfish (Yeh et al, 1996;Cattaert et al, 2010), the status-dependent changes in Mauthner excitability have been linked to status-dependent changes in serotonergic modulation (Whitaker et al, 2011). Other proximate mechanisms may result from the kinds of status-related differences in the nervous system already observed in many animals, including transmitter or neuromodulator concentration (Gutzler et al, 2010), receptor populations (Spitzer et al, 2005;Burmeister et al, 2007), changes in neuronal size and shape (White et al, 2002), neurogenesis (Kozorovitskiy and Gould, 2004;Song et al, 2007), and gross brain morphology (Holmes et al, 2007;O'Donnell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%